Effects of Performance Appraisal on Remuneration Practices and its Impact on Motivation of Employees in Public and Private Sector Companies in Kosovo - Sylqa, Driton; Neziraj, Emin (Journal of Education Culture and Society, 2022)
Aim. The aim of this paper is to investigate the effects of reward policies that are based on performance evaluation of employees. The study links employee performance appraisal with remuneration and other used features for capacity building of employees.Methods. The research consists of primary and secondary data, according to the quantitative method with deductive approach by using the comparison of correlation in analysis. Apart from literature review, the research involves surveys with different entities that would bring an insight into the present situation pertaining to reward practices.Results. The study confirms the significance of the problem between performance evaluation and reward, since there is a weak connection between reward systems and employee’ needs. The majority of respondents approve that reward is bound to the systematic performance appraisal. Results indicate that work experience, acquired knowledge and skills are more often being used, based on high correlation coefficient .435-.784. The ANOVA model shows the accuracy of the regression model with the significance p < .001, whereas the value of independent variables, 66.766 may be used for further research.Conclusions. There is a slight difference between public and private companies concerning the research phenomenon, which makes it a good topic for further research in this field. Based on the study outcomes, we recommend that managers can use promotion as a tool to motivate employees to perform at a higher level and attain their work objectives, especially those that operate in the private sector.